MICROPROPAGATION OF TAVERNIERA CUNEIFOLIA ( ROTH) ARN. ; A SUBSTITUTE FOR COMMERCIAL LIQUORICE - VIJAY C. JAMDHADE; SHRIVARDHAN V. BALKHANDE; BABASAHEB S SURWASE (International Journal of Pharma and Bio Sciences, 2012)
A protocol for in vitro micropropagation was developed for Taverniera cuneifolia (Roth) Arn; a substitute for commercial liqorice- Glycyrrhiza glabra, using nodal explants derived from in vitro raised 30 days old seedlings. The excised axillary tips were cultured on Murashige and Skoog (MS) medium containing BA, Kinetin alone or in combination with AgNo3 for multiple shoot induction. The best condition for shoot growth was with 2 mgl-1 BA and 5.07 mgl-1 AgNo3 in MS medium. Averages of 5.36 shoots were obtained per explant after 30 days of culture. The rooting of in vitro developed shoots (4 6 cm length) was best in MS medium containing 3 % sucrose and 2 mgl-1 NAA. Micropropagated plants were successfully acclimatized (60 %) within 6 weeks after rooting. The standardized protocol reported in this study may help in the conservation of this plant which is currently exploited from nature.